2004
DOI: 10.1152/ajpheart.00437.2003
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial remodeling after discrete radiofrequency injury: effects of tissue inhibitor of matrix metalloproteinase-1 gene deletion

Abstract: Discrete myocardial lesions created through the delivery of radiofrequency (RF) energy can expand; however, the mechanisms have not been established. Matrix metalloproteinases (MMPs) play an important role in myocardial remodeling, and MMP activity can be regulated by the tissue inhibitors of the metalloproteinases (TIMPs). This study examined the role of TIMP-1 in postinjury myocardial remodeling. Lesions were created on the left ventricular (LV) epicardium of wild-type (WT, 8-12 wk, 129SVE) and age-matched T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…As a result, these mice exhibit reduced contact hypersensitivity response following exposure to specific antigens. In keeping with this observation, it was demonstrated that scar maturation was impaired following a discrete radiofrequency-induced myocardial injury (287). Specifically, scar volumes were increased in MMP-3 null mice at 3 days following myocardial injury and were accompanied by reduced inflammatory cell infiltration.…”
Section: A Targeted Gene Deletion Of Mmpsmentioning
confidence: 53%
See 4 more Smart Citations
“…As a result, these mice exhibit reduced contact hypersensitivity response following exposure to specific antigens. In keeping with this observation, it was demonstrated that scar maturation was impaired following a discrete radiofrequency-induced myocardial injury (287). Specifically, scar volumes were increased in MMP-3 null mice at 3 days following myocardial injury and were accompanied by reduced inflammatory cell infiltration.…”
Section: A Targeted Gene Deletion Of Mmpsmentioning
confidence: 53%
“…The effects of TIMP-1 gene deletion were likely due to loss of MMP inhibitory control, since pharmacological MMP inhibition instituted in the post-MI period yielded a myocardial phenotype similar to reference wild-type animals (173). In a discrete myocardial injury model, where significant LV dilation and dysfunction are absent, TIMP-1 null mice exhibited a greater degree of matrix remodeling within and around the site of injury (287). With respect to TIMP-3 gene deletion, a much more significant phenotype becomes manifest (106).…”
Section: B Targeted Gene Deletion Of Timpsmentioning
confidence: 97%
See 3 more Smart Citations